Piero Calamandrei and the interim protection - Caponi, Remo (2016)
The notable contribution of Piero Calamandrei to the study of precautionary protection is weighed in the work Introduzione allo studio sistematico dei provvedimenti cautelari, considered a classic in the literature of civil procedural law. The author reflects on the ability of synthesis and systematic character of Calamandrei's thought that even today, through the European experience, constitutes a reference model that has contributed decisively to the distinction of precautionary measures, which are aimed at guaranteeing the effectiveness of the jurisdictional function.